FORMATION OF THE CONCEPT IN THE SPHERE OF ECOLOGICAL-ORIENTED INNOVATIVE DEVELOPMENT OF REGIONS OF THE RUSSIAN FEDERATION - M. O. Shevchenko (Вестник университета)
A relevance of development new meanings on the trajectory of sustainable development of economy of the Russian Federation has been justified. It has been offered to introduce into circulation a concept from area of the eco-oriented innovative development (further - EOID) of a look “a system -a model - a strategy - an algorithm”. Components of the offered concept have been presented. Verbalization of the specified concept has been considered. Semantic elements of a conceptual framework of the considered concept have been adduced. An application of developed concept on the example of investigation of status and level of implementation of the eco-oriented innovative development (EOID) of one region of the country has been demonstrated. Communication of concepts of this subject area and innovative policy of regions of the country has been shown.